Epidemiology of Oral Cavity Malignancies in Adolescents and Young Adults in Jordan: A Population-Based Study - Burgan, Samar (Jordan Medical Journal, 2024)
Background: Oral cavity malignancies mostly affect older adults and the elderly. Adolescents and young adults (15–39 years) are less affected. However, there is a paucity of studies addressing the epidemiology of oral cavity malignancies in these age groups. Objectives: To describe the epidemiology of oral cavity malignancies in adolescents and young adults in Jordan. Patients and methods: The records of ordinarily resident patients in Jordan aged between 15 and 39 years, with histologically confirmed oral cavity malignancies, between the years 2000 and 2017, were analyzed. The frequency of each type of malignancy, incidence, annual percentage, site, age, sex and trends were analyzed. Results: Between the years 2000 and 2017, 406 adolescents and young adults fulfilled the inclusion criteria. This comprised 2.9% of all cancers in this age category during the same period. The mean age was 28.5 ± 7.6 years. Some 59.4% were male and 40.6% female. Regarding marital status, 34.2% were single, 61.6% married, and 0.7% divorced, while the marital status of 3.4% was unknown. Most (98.3%) were Jordanian nationals. The number of cases increased from 4.7% in 2000 to 6.2% in 2017, with no statistically significant trend. The overall age-adjusted incidence rate was 7.8 per 1,000,000. It decreased from 9.4 in 2000 to 6.2 in 2017, with no statistically significant trend over the study period. Nasopharyngeal cancer was the most common (56.9%), followed by cancers of the salivary gland (16.7%), tongue (10.3%), gums (6.2%), lips (5.2%), hypopharynx (2.7%), other oral cavity and pharynx (1.0%), oropharynx (0.5%), floor of mouth (0.2%), and tonsils (0.2%). Overall, the incidence of cancers of the oral cavity and pharynx was higher in males. The incidence of cancers of the nasopharynx, tongue, and lips was higher in males, while salivary gland cancer was higher in females. The incidence of cancers of the gum, hypopharynx, and pharynx did not differ between the sexes. Conclusions: The incidence of oral malignancies in adolescents and young adults in Jordan is relatively high compared to worldwide estimates but is not increasing. Risk factors for these malignancies should be the target of primary prevention interventions.